The strategic applications of natural polymer nanocomposites in food packaging and agriculture: Chances, challenges, and consumers’ perception - Wypij, Magdalena; Trzcińska-Wencel, Joanna; Golińska, Patrycja; Avila-Quezada, Graciela Dolores; Ingle, Avinash P.; Rai, Mahendra (Frontiers in Chemistry, 2023)
Natural polymer-based nanocomposites have received significant attention in both scientific and industrial research in recent years. They can help to eliminate the consequences of application of petroleum-derived polymeric materials and related environmental concerns. Such nanocomposites consist of natural biopolymers (e.g., chitosan, starch, cellulose, alginate and many more) derived from plants, microbes and animals that are abundantly available in nature, biodegradable and thus eco-friendly, and can be used for developing nanocomposites for agriculture and food industry applications. Biopolymer-based nanocomposites can act as slow-release nanocarriers for delivering agrochemicals (fertilizers/nutrients) or pesticides to crop plants to increase yields. Similarly, biopolymer-based nanofilms or hydrogels may be used as direct product coating to extend product shelf life or improve seed germination or protection from pathogens and pests. Biopolymers have huge potential in food-packaging. However, their packaging properties, such as mechanical strength or gas, water or microbial barriers can be remarkably improved when combined with nanofillers such as nanoparticles. This article provides an overview of the strategic applications of natural polymer nanocomposites in food and agriculture as nanocarriers of active compounds, polymer-based hydrogels, nanocoatings and nanofilms. However, the risk, challenges, chances, and consumers’ perceptions of nanotechnology applications in agriculture and food production and packaging have been also discussed.